Photonic Materials for Sensing, Biosensing and Display Devices - Serpe, Michael J.; Kang, Youngjong; Zhang, Qiang Matthew (Springer Series in Materials Science,, 2016)
This book presents the basics and applications of photonic materials. It focuses on the utility of these devices for sensing, biosensing, and displays. The book includes fundamental aspects with a particular focus on the application of photonic materials. The field of photonic materials is both a burgeoning, and mature field. There are new advances being made on a daily basis, all based on the fundamental roots set by work by those like Ozin, Thomas, Asher, and others.